Early Predictive Value of the Glucose‐to‐Lymphocyte Ratio for the Occurrence of Stroke‐Associated Pneumonia - Fuqiang Zhou; Liju Ma; Min Li; Haijiang Li; Heying Yang; Ye Xu; Kuankuan Dang; Fengchen Gao; Haimei Sun (Brain and Behavior)
ABSTRACT Background and Objective Hyperglycemia and poststroke immunosuppression can lead to a decline in immune function, resulting in an increased incidence of infectious events. The relationship between the glucose‐to‐lymphocyte ratio (GLR), a novel indicator, and stroke‐associated pneumonia (SAP) remains unclear. The objective of this study is to investigate the early predictive value of the GLR in the context of SAP. Methods A retrospective analysis was conducted on acute stroke patients admitted to the Department of Neurology at the First Affiliated Hospital of Kunming Medical University from 2017 to 2021. The dataset included demographic information, vascular risk factors, and laboratory test results. Logistic regression analysis was used to assess the correlation between the GLR and the incidence of SAP. The GLR was converted into a categorical variable for trend testing, and compared the predictive efficiency of GLR through the receiver operating characteristic (ROC) curve and Bonferroni correction analysis. Results This study included 711 patients with acute stroke according to a 1:2 case–control ratio, with 237 (33.3%) in the SAP group and 474 (66.7%) in the Non‐SAP group. The baseline level of the GLR was significantly greater in the SAP group than in the Non‐SAP group (p < 0.001). After correction using multifactorial logistic regression analysis, GLR (OR: 1.182, 95% CI: 1.090–1.281, p < 0.001) was identified as an independent risk factor for SAP. When GLR was converted into a categorical variable, the risk of SAP in group Q3 was 3.210 times greater than that in group Q1, and the trend test yielded p < 0.001. The analysis of the ROC curve revealed that the area under the curve (AUC) for the GLR was 0.737, with a sensitivity of 70.0% and specificity of 67.1% at a cutoff value of 4.110. The predictive efficacy of the GLR for SAP patients was superior to that of either blood glucose or lymphocyte counts alone (p < 0.0167). Conclusions An elevated GLR within 24 h of hospital admission following an acute stroke is an independent risk factor for SAP. The risk of SAP increases progressively with increasing GLR, suggesting that the GLR may have a certain early predictive value for the occurrence of SAP.